1992
DOI: 10.1111/j.1432-1033.1992.tb17494.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence‐specific 1H‐NMR assignment and determination of the secondary structure of bovine heart fatty‐acid‐binding protein

Abstract: The nearly complete sequence‐specific 1H resonance assignment of the pI = 4.9 isoform of cytosolic 15‐kDa fatty‐acid‐binding protein from bovine heart (H‐FABPc) by homonuclear two‐dimensional NMR spectroscopy is presented. Regular secondary structure elements were identified from NOE spectra and the sequence locations of slowly exchanging backbone amide protons. The molecular structure of the protein was found to consist mainly of ten antiparallel β‐strands and two short α‐helices. The data presented here for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In addition, chemical shift heterogeneity was observed in the NMR spectra for each isoform of bovine H-FABP. For the pI 4.9 isoform, multiple peaks were observed at positions 22 to 36, 53 to 60 and 119 to 122 (Lü cke et al, 1992). Based on these findings, it was concluded that helix II and adjacent portions of the molecule maintain four distinct backbone conformations with lifetimes of at least 10 ms (Lassen et al, 1993).…”
Section: Comparison To the Structures Of Homologous Proteinsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, chemical shift heterogeneity was observed in the NMR spectra for each isoform of bovine H-FABP. For the pI 4.9 isoform, multiple peaks were observed at positions 22 to 36, 53 to 60 and 119 to 122 (Lü cke et al, 1992). Based on these findings, it was concluded that helix II and adjacent portions of the molecule maintain four distinct backbone conformations with lifetimes of at least 10 ms (Lassen et al, 1993).…”
Section: Comparison To the Structures Of Homologous Proteinsmentioning
confidence: 93%
“…This protein shares 30% sequence identity with rat I-FABP. The H-FABP structure was based initially on 1071 restraints derived from 2-D 1 H spectra of an unenriched sample (Lü cke et al, 1992;Lassen et al, 1993) and subsequently, 2371 restraints derived from 2-D 1 H and 3-D 15 N-resolved spectra of a uniformly 15 N-enriched sample (Lassen et al, 1995). The overall fold was the same as observed here for I-FABP, but some differences were noted in the conformation of the bound ligand and several other regions of the protein.…”
Section: Comparison To the Structures Of Homologous Proteinsmentioning
confidence: 93%
“…Apparently, the experimental conditions in the previous NMR study ( 28 ) did not allow the observation of several crucial NOE connectivities, thus pointing to a disordered conformation rather than to a helical fold. Other members of the i-LBP family also featured weak signal intensities of the backbone amides belonging to helix ␣ II, as they frequently either exhibit strong line-broadening or exist as several distinct spin systems ( 21,25,51,53 ). This may be the consequence of a high degree of conformational variability observed in this specifi c segment of the apo protein ( 26,45 ) and/or a fast exchange of the amide protons with water, as helix ␣ II exhibits a more pronounced solvent exposure than the other secondary structure elements of the typical i-LBP fold.…”
Section: Discussionmentioning
confidence: 99%
“…In order to check the structural integrity of the H-FABP mutants, we have collected 1D and 2D NMR spectra. On the basis of the NMR proton resonance assignment of bovine H-FABP [20], the complete "H assignment of human H-FABP (89 % sequence identity) was obtained at pH 5.5 and 37 mC. Because of decreased sample stability of various mutants at low pH and high temperature, the experimental conditions were eventually adjusted to pH 7.0 and 25 mC for all samples in order to ensure the comparability of the results.…”
Section: Nmr Analysismentioning
confidence: 99%